Endometriosis of the Vermiform Appendix within a Hernia Sac Infiltrating the Pubic Bone. (19th January 2015) - Ziaja, Damian; Bolkowski, Tomasz; Januszewski, Krzysztof; Skrzypulec-Plinta, Wioletta; Chudek, Jerzy; Ziaja, Krzysztof
Abstract : Purpose . Appendicular endometriosis mimicking appendicitis is a rare finding. Inguinal tumor in the course of appendicular endometriosis located within an inguinal hernia sac and infiltrating the periosteum of the pubic bone has not yet been described. Case Report . This paper describes a case of a rapidly enlarging, solid, unmovable, very painful upon palpation inguinal tumor, in a 36-year-old nulliparous woman. During surgery, a hard (approximately 4 cm in diameter) tumor infiltrating the periosteum of the right pubic bone and continuous with the inguinal hernia sac was dissected. The distal segment of the vermiform appendix was an element of the dissected tumor. Histological examination revealed endometriosis of the distal vermiform appendix. After 6 months of hormone treatment, she was referred for reoperation due to tumor recurrence. Once again histological examination of the resected tissue revealed endometriosis. There was no further recurrence of the disease with goserelin therapy. In addition to the case report, we present a review of the literature about endometriosis involving the vermiform appendix and the inguinal canal (Amyand's hernia). Conclusion . This case expands the list of differential diagnoses of nodules found in the inguinal region of women.